2020
DOI: 10.18632/aging.202136
|View full text |Cite
|
Sign up to set email alerts
|

Influence of aging on deterioration of patients with COVID-19

Abstract: Aging is an important factor affecting the deterioration of patients with coronavirus disease 2019 (COVID-19). The aging and degeneration of various tissues and organs in the elderly lead to impaired organ function. Underlying conditions such as chronic lung disease, cardiovascular disease, and diabetes in aged patients are associated with higher mortality. Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) primarily interacts with the cell surface receptor angiotensin-converting enzyme (ACE) 2 and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 105 publications
1
16
0
2
Order By: Relevance
“…This information has greatly promoted the research progress of aging in COVID-19 and has great significance in clinical application. Pang et al also agrees with the former, suggesting that altered receptor signals in aging and chronic disease play a role in COVID-19 infection and are associated with an increased risk of deterioration in different organs [ 46 ]. Thus, they concluded that aging may contribute to the deterioration of COVID-19 in older patients.…”
Section: Discussionsupporting
confidence: 53%
“…This information has greatly promoted the research progress of aging in COVID-19 and has great significance in clinical application. Pang et al also agrees with the former, suggesting that altered receptor signals in aging and chronic disease play a role in COVID-19 infection and are associated with an increased risk of deterioration in different organs [ 46 ]. Thus, they concluded that aging may contribute to the deterioration of COVID-19 in older patients.…”
Section: Discussionsupporting
confidence: 53%
“…SARS-CoV-2 employs a host cell surface protein, angiotensin-converting enzyme (ACE) 2, as a receptor for cellular entry 11 . A number of recent studies have suggested that the expression of ACE2 is both tissue and age-dependent 12, 13 , and differences in ACE2 expression between children and adults were proposed to contribute to less severe disease in children. At single cell level, viral entry genes were shown to be most highly expressed in the nasal epithelium in healthy adults 14 .…”
Section: Introductionmentioning
confidence: 99%
“…Age is a special and important factor in the lifetime of humans, which is characterized with inevitable and internal steady growth. In the different phases of life cycle (young, adult and old), individuals present different biological characteristics and disease risk [ 24 , 25 ]. Previous studies have suggested that age could affect the microbial composition and functions in the mouse and cynomolgus macaques [ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%